The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1109/tasc.2011.2178975
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Field in the Winding of an YBCO Pancake Coil: Experiments and Calculations

Abstract: The AC loss is an important issue for many applications containing coils of ReBCO coated conductors, specially transformers. In order to reduce the AC loss, it is necessary to understand the loss mechanisms. We measured and computed the radial magnetic field component in a pancake coil with a net transport current, as this component of the magnetic field plays a crucial role in the AC loss. For this purpose, we prepared a small pancake coil wound with 12 mm wide YBCO tape with non-magnetic substrate and measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…This method assumes the critical-state model in its most general condition, that is |J| can take any value lower or equal to J c [20,21]. The main developments to compute superconducting coils are in [22], the implementation of a field dependent J c in [23], interaction with linear magnetic materials in [24], and non-uniform tape properties in [25]. The present work assumes constant J c for simplicity.…”
Section: Methodsmentioning
confidence: 99%
“…This method assumes the critical-state model in its most general condition, that is |J| can take any value lower or equal to J c [20,21]. The main developments to compute superconducting coils are in [22], the implementation of a field dependent J c in [23], interaction with linear magnetic materials in [24], and non-uniform tape properties in [25]. The present work assumes constant J c for simplicity.…”
Section: Methodsmentioning
confidence: 99%
“…We have cut three rectangular samples from the same section of the tape, two from the central part and one from the edge (figure 6). The cutting was done by a procedure described in [8] which does not markedly degrade the superconductor near the cuts.…”
Section: Inductive Measurement Of Critical Current Densitymentioning
confidence: 99%
“…Here we nevertheless investigate another aspect of superconductor non-uniformity. It was pointed out by several groups studying the AC loss that some of the experimental results could be explained assuming a variation of the critical current density across the tape width [5][6][7][8]. In other words, the critical current at the longitudinal location z = z 0 should be obtained by integrating the position-dependent sheet current density (2) across the tape width, w SC :…”
Section: Introductionmentioning
confidence: 99%
“…However, this simple scaling is often inaccurate, due to the fact that the critical current is not homogeneous across the width of the tape. The lateral inhomogeneity of the critical current across the tape width in coated-conductors has been reported and investigated in several articles [28][29][30][31][32][33]. Those studies showed that the central part of the tape has usually higher critical current than the lateral parts.…”
Section: Ic Measurement and Model Implementationmentioning
confidence: 99%